Messinian biostratigraphy based on foraminifera and ostracodes in Ionian zone of Albania - BULI, K.; PRILLO, S.; BULl, Ν.; KUMATI, L.; ROQl, R. (Bulletin of the Geological Society of Greece, 2018)
Messinian biostratigraphy based on foraminifera and Ostracodes was studied in several surface sections within Peqin-Durres region. The sections are located in the eastern and northwestern part of the Peri-Adriatic Foredeep (PAF) of Albania (FigJ ). The Thartor section is located more or less in the center of the region studied. Its Messinian sediments in particular late Messinian one are well exposed and just in this place they represent the boundary of great differences between these sediments and those that could be occurred towards east or towards south. Firstly, here well distinguished the preevaporitic sequence which very rapidly wedge-out towards southeast. Secondly, here is the latest southeast boundary of gypsum blocks occurrence. Moreover in this section the lack of "lago-mare" biofacies is apparently owing to its erosion. Towards northern and western sections the lower boundary of "lago-mare" biofacies is well determined lithologically and faunistically. Towards southeast and eastern sections this boundary determined also by first occurrence of Cyprideis, Candona etc., as above but it seems to be not synchronous from section to section. In this aspect this "lago-mare" biofacies is more similar with a Paratethyan biofacies. Within the gypsum bearing region "lago-mare" biofacies is focused in the latest Messinian only, in this aspect it could be called "Tethyan lago-mare' biofacies.